Gastric Cancer: Generalities, Traditional Treatments, and Biological Therapies as New Therapeutic Options - Aguilar Murillo, Raquel (2022)
Gastric cancer is one of the most frequent types worldwide. It is the fourth most common and the second most deadly. Costa Rica is the leading country where this pathology is diagnosed in Central America. Its development involves nutritional, genetic, and environmental factors, among others. Traditional treatments are based on surgery (considered first-line), radiotherapy, and chemotherapy. In recent years, work has been done on new biological therapies to improve the patients' quality of life and survival. Advances have been achieved in the field of microRNAs, in which there is a promising future. The most studied have been miR-218, miR-375, and miR-7, diminished in gastric tumors. As a complement, vaccines have been developed, including rMVHu191 and G17DT. Many have required the incorporation of adjuvants to enhance the immune response. Finally, monoclonal antibodies have been considered for distinct targets related to this disease. Of these molecules, only trastuzumab, ramucirumab, nivolumab, and pembrolizumab have approval against this illness. Although there is still a long way ahead, soon will be more available options.